Integrated components of high speed camera - Naveen Tamizh Kannan (Nanyang Technological University, 2024)
In this project, a small-scale investigation was carried out to study machine vision systems that can be used for Wyn Monde Pte Ltd to produce a machine vision camera, focusing on the specific requirements provided. The identification of crucial elements necessary for manufacturing a high-speed camera, including various types of image sensors, formed a key part of the study. The project also detailed the examination and comparison of these image sensors. Through thorough research, the integration of components utilizing these image sensors in the high-speed camera was explored, along with an analysis of their capabilities for high-speed camera applications. The insights such as studying the types of image sensors, performance factors of image sensors and setting up of machine vision systems provided a deeper understanding of individual components and their integration. Consequently, this knowledge facilitated an analysis of the costs associated with acquiring and integrating these components to produce a machine vision system for Wyn Monde Pte Ltd on a small scale.